Working Memory, Vocabulary Breadth and Depth in Reading Comprehension: A Study with Third Graders. Issue 9 (21st October 2022) - Artuso, Caterina; Palladino, Paola
ABSTRACT: In the current study, we investigated the role of vocabulary knowledge in the relation between working memory (WM) and reading comprehension, in a sample of 55 typically developing 8-year-old Italian children. The role of WM in comprehension is well-established, as both involve similar processes for successful task performance (i.e., active maintenance of relevant information, while inhibiting irrelevant material). Less investigated is the role of vocabulary knowledge. Here, we considered breadth, (assessed via a naming task) and depth (assessed via similarity and a vocabulary task). Our data showed the strong relation between WM and reading comprehension is mediated by vocabulary depth (but not vocabulary breadth). In addition, we also demonstrated the reverse relationship, that is WM and reading comprehension account for vocabulary depth (but not breadth). These findings have important implications for educational research and contribute to the literature on the nature of reading comprehension.